Machine Learning Pengenalan Herpetofauna Dilindungi Di Indonesia - Hasan, Yasir (UNIKA Santo Thomas, 2023)
The population of herpetofauna animals in Indonesia is decreasing due to hunting, habitat destruction, and illegal trade. Apart from that, there is very little introduction to Herpetofauna among reptiles and amphibian lovers. There are also many cases of ownership and buying and selling of reptiles and amphibians that end with the forced taking of these Herpetofauna animals and even imprisonment for not having permission from the government. The problem of lack of knowledge about the types of Herpetofauna is one of the causes of the rarity of these animals which will become extinct in the future. Therefore, more effective and efficient conservation support efforts are needed in the form of research based on artificial intelligence to identify protected Herpetofauna animals in Indonesia. This research uses Machine Learning technology and the method used for segmentation is Deep Learning which is included in the YOLO stage and is very supportive in edge detection, color change, and classification. The use of this technology is implemented in a GUI application built in Python which can be used as a detection tool for the types of herpetofauna found in nature, in captivity, or in reptile trading markets. Therefore, Machine Learning Research Herpetofauna is very important to contribute to the government's conservation efforts to protect Herpetofauna and is expected to be sustainable for future generations.